Jazz in Kuala Lumpur - Jähnichen, Gisa (Jazz Research Journal, 2012)
This article will focus on the development from ‘doing’ to ‘making’ jazz in Malaysia’s main urban centre Kuala Lumpur. ‘Doing jazz’ is here understood as ‘doing what the others do’, a practice of creating musical equality with existing practices that are considered ‘up-to-date’ in a small world of self-taught jazz musicians of which some were trained abroad. ‘Making jazz’ goes far beyond this understanding. It aims at creating difference and uniqueness in a conscious way, using individual resources related to local culture and history. However, the polarity between imitative and original has many facets resulting from ethnic, religious and social contradictions within the cultural construction of Malaysia. From this perspective, the role of different racial backgrounds and knowledge bases of various audiences and of jazz personalities, together with their self-perception, needs to be examined. Based on a brief outline of the social background and a concise historical overview, questions of shifting identity as well as of musicianship in the specific urban culture of Kuala Lumpur will be raised and discussed. Does the new generation, facing hegemonic representation, develop racially indifferent attitudes towards jazz or does it aspire to contribute a self-determined individuality, accepting the blurring of borders between global jazz and Southeast Asian popular music?